Rancang Bangun Alat Angkut Bahan Baku Guna Meningkatkan Efektivitas Material Handling dengan Pendekatan Ergonomi - Hartono, Moh Arief Andri; Purnama, Jaka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT Candi Jaya Amerta is a company engaged in the food sector and produces various types of traditional crackers, such as shrimp crackers, fish crackers, and other variations. The process of manually transporting flour raw materials at PT CJA takes a long time so that it can reduce the effectiveness of material handling. In this study, the design of an ergonomic raw material transport tool was carried out with the aim of reducing the level of fatigue in workers and speeding up the process of moving raw materials. the method used is the anthropometric method. the results of collecting anhtropometric data on workers are used to design the tool. the cardiovascular load method is used to measure the level of fatigue of workers based on the pulse rate of workers. the dimensions of the tool have a height of 114cm, width of 80cm, length of 125cm, and tool reach of 88cm. the percentage of worker fatigue is known with % CVL before using the tool design. worker 1 = 72.5%, worker 2 = 61.22% then there is a decrease in fatigue levels after using the tool design to %CVL worker 1 = 43%, worker 2 = 26%.